Evaluation of Dynamic Visual Perception of Riverside Interface in Mountainous Cities from the Perspective of Boating - Dan LUO; Ruhong WEI (Fengjing Yuanlin)
ObjectiveThe riverside interface of mountainous cities is an area featuring the integration of natural and artificial elements, where the visual information is highly concentrated and the perception levels are extremely rich. Thus it can be taken as an important sample for visual landscape research. Cruise boat is one of the important ways of viewing in mountainous cities, and the continuous and dynamic visual process during boating can bring unique viewing experience. Compared with other viewing methods, boating has more visual advantages for urban interface viewing, which is an important entry point for visual perception research. The research on the dynamic visual perception of urban interface from the perspective of boating can provide a theoretical basis for the control and improvement of visual landscape in mountainous cities.MethodsTaking the riverside interface of the core area of “Two Rivers and Four Banks” in Chongqing as the research object and the cruise line of Liangjianghui as the movement path, this research connects the perception state and spatial characteristics by combining subjective and objective evaluation indicators, and analyzes the underlying logic of the formation of visual perception results. Starting from interface characteristics from the perspective of boating, the overall interface and visual unit are divided into two evaluation levels. From the three dimensions of visual comfort, readability and characteristic recognition, 14 evaluation indicators are selected, including overall fixation time, sky visibility, skyline fluctuation, color indicator, natural landscape distribution, interface harmony, fixation count, information density, visit count, saccade count, architectural level richness, mountain visibility, characteristic cognition and contour rhythm. The subjective and objective visual perception data with respect to eye movement behavior, questionnaire and spatial indicator are integrated. After the unified classification of the evaluation indicators, the expert scoring method and AHP analytic hierarchy process are used to determine the weight of each evaluation indicator, and finally an evaluation model for dynamic visual perception of riverside interface in mountainous cities is established. The viewing video on the cruise ship is collected as the experimental stimulation material, and the eye tracking experiment is carried out to simulate the viewing state of viewers on the cruise ship. The visual perception data of viewers is collected through questionnaire, and spatial characteristics are quantified through the images of urban riverside interface to obtain the spatial data. After evaluating the different levels of the research interface, the law on dynamic visual perception of riverside interface in mountainous cities from the perspective of boating is summarized. ResultsThrough the overall interface evaluation, this research gains a clear understanding of the current situation of interface perception. It is found that there are significant differences in the readability dimension of each interface, and the changes of boating route and speed affect the readability of interface to a certain extent. At the visual unit scale, the correlation between the difference of perception status and space is further discussed. It is judged that readability may be affected by interface contour, building level richness, landmark building distribution and interface element integrity. By sorting out the space types, it is found that among the five types of visual units, namely the multi-level unit, characteristic unit, concave unit, filling unit and natural unit, the filling unit gets a lower score in the evaluation of interface perception, which is mainly affected by the less change of building level. At the same time, the large area occlusion of the building on the line of sight affects the visual experience. Combined with the eye movement view, the visual law is further summarized: First, the line of sight is often perceived from top to bottom, and the visual focus is concentrated in the middle and lower parts of the interface, which is related to the distribution of more landscape elements with significant characteristics in these parts, including landmark buildings, riverbank forms, river beaches and cruise ships. Secondly, the spatial level is an important perception content, involving the connection between buildings, between buildings and roads, between buildings and riverbanks, and between riverbanks and water surfaces. In addition, the gaps in the building interface are also an important perception object. They enable the line of sight to penetrate into more urban space and enrich the changes of architectural level.ConclusionBased on what mentioned above and in combination with the current spatial situation and perception patterns, an overall optimization strategy for readability is proposed from the two aspects of rhythm control and feature optimization. Moreover, the research also provides optimization suggestions for important visual enhancement points such as the intersection of different levels of space, cruise ships, riverbanks, plants, water surfaces, characteristic buildings, and riverbank forms within each unit. The research forms a technical path for both perception evaluation and spatial optimization, which may provide a theoretical support and practical guidance for the construction of livable mountain cities.